the cultural discourse of Malek Bennabi- A critical approach- - tifoura, asma; toufouti, shahrazed (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
this article aims to approach the cognitive foundations on which Malek Bennabi’s cultural thinking is based, based on the statements and propositions on which he built his comprehensive vision of the intellectual renaissance project. Anyone who examines Malek Bennabi’s writings . He realizes the cognitive momentum that he took for an insightful vision to address the problems of the Islamic reality. In this context, the influence of the cultural, social, historical and political contexts in formulating his path towards dismantling the crisis of the Muslim individual in the face of the multiple constraints of reality becomes clear.